Investigation of glycan evolution based on a comprehensive analysis of glycosyltransferases using phylogenetic profiling - Tomono, Takayoshi (Biophys Physicobiol, 2015)
Glycans play important roles in such cell-cell interactions as signaling and adhesion, including processes involved in pathogenic infections, cancers, and neurological diseases. Glycans are biosynthesized by multiple glycosyltransferases (GTs), which function sequentially. Excluding mucin-type O-glycosylation, the non-reducing terminus of glycans is biosynthesized in the Golgi apparatus after the reducing terminus is biosynthesized in the ER. In the present study, we performed genome-wide analyses of human GTs by investigating the degree of conservation of homologues in other organisms, as well as by elucidating the phylogenetic relationship between cephalochordates and urochordates, which has long been controversial in deuterostome phylogeny. We analyzed 173 human GTs and functionally linked glycan synthesis enzymes by phylogenetic profiling and clustering, compiled orthologous genes from the genomes of other organisms, and converted them into a binary sequence based on the presence (1) or absence (0) of orthologous genes in the genomes. Our results suggest that the non-reducing terminus of glycans is biosynthesized by newly evolved GTs. According to our analysis, the phylogenetic profiles of GTs resemble the phylogenetic tree of life, where deuterostomes, metazoans, and eukaryotes are resolved into separate branches. Lineage-specific GTs appear to play essential roles in the divergence of these particular lineages. We suggest that urochordates lose several genes that are conserved among metazoans, such as those expressing sialyltransferases, and that the Golgi apparatus acquires the ability to synthesize glycans after the ER acquires this function.